2019
DOI: 10.1186/s40851-019-0141-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis suggests that the sperm-specific sodium/proton exchanger and soluble adenylyl cyclase are key regulators of CatSper among the Metazoa

Abstract: Background CatSper is a sperm-specific calcium ion (Ca 2+ ) channel, which regulates sperm flagellar beating by tuning cytoplasmic Ca 2+ concentrations. Although this Ca 2+ channel is essential for mammalian fertilization, recent bioinformatics analyses have revealed that genes encoding CatSper are heterogeneously distributed throughout the eukaryotes, including vertebrates. As this channel is activated by cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 96 publications
3
24
0
Order By: Relevance
“…5, Table 5). These findings support the hypothesis of Romero and Nishigaki that CatSper3, sNHE, and sAC form prototypical machinery for sperm flagellar beating in metazoans [87]. This study further identified the gene encoding creatine kinase, flagellar, which was first identified from flagella of sea urchin sperm, participating in energy transport from sperm heads to the flagella during sperm motility [89].…”
Section: Upregulated Genes In Mature Testessupporting
confidence: 88%
See 2 more Smart Citations
“…5, Table 5). These findings support the hypothesis of Romero and Nishigaki that CatSper3, sNHE, and sAC form prototypical machinery for sperm flagellar beating in metazoans [87]. This study further identified the gene encoding creatine kinase, flagellar, which was first identified from flagella of sea urchin sperm, participating in energy transport from sperm heads to the flagella during sperm motility [89].…”
Section: Upregulated Genes In Mature Testessupporting
confidence: 88%
“…Spermiogenesis is a process by which haploid spermatids undergo a complex series of morphological changes, and eventually become elongated functional sperm. The Testis-specific serine/threonine-protein kinase 1 CL2440.Contig1_All [78,79] Testis-specific serine/threonine-protein kinase 2 Unigene8363_All [78,79] Outer dense fiber protein 2 CL11766.Contig4_All [80] Alstrom syndrome protein 1 CL2440.Contig1_All [81] Radial spoke head 1 homolog CL2440.Contig1_All [82] Dynein regulatory complex protein 9 CL4871.Contig6_All [83] Sperm motility/capacitation Dynein regulatory complex subunit 7 CL8060.Contig33_All [86] Sodium/hydrogen exchanger 10 CL11505.Contig1_All [87] Creatine kinase, flagellar CL12240.Contig1_All [88] Adenylate cyclase type 10 CL1089.Contig3_All [87] Cation channel sperm-associated protein 3 Unigene27629_All [87] Cyclin-F Unigene55093_All [89] Dynein regulatory complex subunit 4 Unigene7541_All [90] Chromosome structure Histone H2A CL4659.Contig4_All [120] Fertilization process Hapless 2 CL1879.Contig3_All [109,110] Receptor guanylate cyclases CL4659.Contig4_All [22] Cyclic nucleotide-gated channel cone photoreceptor subunit alpha CL3457.Contig2_All [153] Steroidogenesis Steroid 17-alpha-hydroxylase/17,20 lyase Unigene38823_All [104] presence of spermaries having both round spermatids and mature sperm in testes collected in June 2017 suggested that spermiogenesis was occurring in the testes at the time of collection, and that genes involved in regulation of spermiogenesis were being expressed in testes.…”
Section: Characteristics Of Mature Testes As Assessed By Histologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…5, Table 5). These ndings support the hypothesis of Romero and Nishigaki that CatSper3, sNHE, and sAC form prototypical machinery for sperm agellar beating in metazoans [76]. This study further identi ed the gene encoding creatine kinase, agellar, which was rst identi ed from agella of sea urchin sperm, participating in energy transport from sperm heads to the agella during sperm motility [77].…”
Section: Upregulated Genes In Mature Testessupporting
confidence: 85%
“…The CatSper Ca 2+ channel is a sperm specific Ca 2+ channel highly conserved in mammals (Cai and Clapham, 2008), but also present in a wide range of other species (Romero and Nishigaki, 2019). Ca 2+ signaling is a key regulator of sperm function and CatSper thus controls important sperm functions (Lishko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%